Ferrate modified carbon felt as excellent heterogeneous electro-Fenton cathode for chloramphenicol degradation. (1st December 2022) - Zhang, Jingjing; Wang, Dongbo; Zhao, Feiping; Feng, Jing; Feng, Haopeng; Luo, Jun; Tang, Wangwang
Highlights: Ferrate modified carbon felt cathode was innovatively used for heterogeneous EF process. The Fe-CF/EF system exhibited excellent performance for chloramphenicol degradation. The Fe-CF cathode exhibited good recyclability and outstanding practicability. Toxicity assessment confirmed an efficient toxicity reduction after 60 min treatment. Main reactive species and possible mechanism for CAP degradation were analyzed. Abstract: In this study, a novel and efficient heterogeneous electro-Fenton (EF) process with a potassium ferrate (K2 FeO4 ) modified carbon felt (Fe-CF) cathode was developed for chloramphenicol (CAP) removal. The catalytic activity was assessed by the comparison of different systems and the effects of multiple operating parameters (K2 FeO4 dosage, initial solution pH, applied current) and co-existing constituents. Results indicated that the Fe-CF cathode exhibited excellent performance for CAP degradation (almost 100% removal efficiency within 60 min) over a wide range of pH (pH 3–9) during heterogeneous EF ascribed to the synergistic effect of embedded iron species and porous graphitic carbon structure and effective utilization of the in-situ generated H2 O2 . Moreover, the Fe-CF cathode possessed good recyclability with low metal leaching (98.2% CAP removal efficiency after reused for 5 times) and outstanding real water application performance. The ∙OH and O2 ∙ − were responsible for CAP degradation, while ∙OH played a main role. Moreover, the toxicity evaluation by E. coli growth experiments demonstrated an efficient toxicity reduction in this system. Overall, a novel heterogeneous EF functional cathode with superior performance was fabricated via a green, low-cost one-step method, which shows promising application potential for actual wastewater treatment. Graphical abstract: Image, graphical abstract